Photography [ theoretical snapshots - Long, J. J. [ (Jonathan James)] , 1969-; Noble, Andrea; Welch, Edward , 1973- (Routledge, 2009)
Offers perspectives on photography theory from some of the world's leading critics and theorists. Ranging from the most personal to the most dehumanized uses of photography, from the 19th century onwards, and from Latin America to Northern Europe, this title is suitable for those interested in photography, visual culture, and cultural history